교육콘텐츠 개발을 위한 茶山 丁若鏞 家庭生活觀에 대한 考察 - 주영애(Young-Ae Ju) (한국콘텐츠학회 논문지, 18(6), 2018)
본 연구는 다산 정약용의 가정생활관을 고찰하여 그 의의를 찾고, 실천성에 대해 논의하였다. 다산의 가정생활관은 다산시문집, 편지글, 선행연구 등을 참고하여 가족관, 의식주생활관, 가정경제관으로 나누어 살펴보았다. 다산의 가정생활관은 자기관리와 절제, 근검절약과 분수 지키기, 순리적인 나눔과 베품으로 정리할 수 있었으며, 일상에서 실천적인 노력이 강조되었다. 첫째 자기관리와 절제는 말과 행동을 조심하기, 효를 실천하기, 가족 간에 화목하기, 독서하기, 선함을 잃지 않기, 심신을 수양하기 포기하기 말고 독립적이고 당당하기, 용모와 안색을 바르게 하기 등이다. 둘째로 근검절약과 분수는 항상 부지런 하고, 검소한 생활을 실천하며, 사치를 금하고 자신의 일을 열심히 하며, 과음을 경계한 것이다. 셋째는 순리적인 나눔과 베품의 실천은 환경을 탓하지 말고 분수에 맞게 지내고, 곤궁함에 대처하며, 사욕을 막고 나누고 베풀어 주라는 것이었다. 이와 같은 다산의 가정생활관은 오늘날 공유가치, 공동체사회, 복지사회를 구현해 가기 위한 규범과 가치를 담고 있다고 사료된다. 앞으로 다산의 가정생활관에 대한 교육콘텐츠의 개발을 위해 본고가 활용될 수 있을 것으로 보며, 이를 통해서 시대를 초월한 다산 정신이 계승되고 실천될 수 있기를 기대한다. In this research, the significance and practice on life of Dasan Jeong Yak-Young’s family is reviewed. Articles, letter, poetry written by Dasan and research papers regarding to him are mainly referred for the research. Family life consciousness is divided into three sections in terms of family, food clothing and shelter life, and the economy of the family. Dasan’s family life consciousness has been organized with self-management, temperance, thrift, sharing and giving for family and others. He emphasized practical efforts in daily life to realize sense of family life. First, Dasan sought self-managing and temperance as follows. He suggested attitude of careful speech and behavior, filial duty, peace within a family, reading, and training the body and mind including nice and independent temperament with being in good shape. Second, Dasan has been taught to practice the following to save money. It is important to be diligent, to live a simple life, to work hard on one’s work, and to avoid extravagant behavior and heavy drinking. Third, Dasan emphasized to practice rational sharing and giving. It is to adapt to the environment, to live within one's means, to cope with difficult circumstances, not to have desire, and to practice giving. Dasan's family life consciousness includes the rules and values for implementing a welfare society. The welfare society is a society that shares good values and practices norms. In the future, the content of education should be developed to provide education about Dasan’s family life consciousness. I hope this study can provide an opportunity that the moral teachings of Dasan can be handed down and practiced in relation to family life. KCI Citation Count: 1